2012
DOI: 10.1063/1.4769837
|View full text |Cite
|
Sign up to set email alerts
|

Microwave reflection imaging using a magnetic tunnel junction based spintronic microwave sensor

Abstract: A far-field microwave imaging technique has been developed using a spintronic sensor based on a magnetic tunnel junction (MTJ). Such a sensor can directly rectify a microwave field into a dc voltage signal using the Seebeck effect. Thanks to the high conversion efficiency of the microwave rectification in MTJs, the microwave power sensitivity of the spintronic sensor is on the order of 1–10 mV/mW. This high sensitivity allows the sensor to directly measure the coherent spatial scattered microwave field distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Differing from these static transport measurements, Zhang et al performed a dynamic experiment and demonstrated magneto-Seebeck rectification in MTJs, which converts microwaves to a dc voltage through the thermal dynamics. This observation not only motivates the theoretical investigation of thermal-spin and thermoelectric properties (such as figures of merit) of MTJs driven by microwave fields [13], but also paves the way for utilizing spin caloritronics in microwave imaging applications [15,16].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Differing from these static transport measurements, Zhang et al performed a dynamic experiment and demonstrated magneto-Seebeck rectification in MTJs, which converts microwaves to a dc voltage through the thermal dynamics. This observation not only motivates the theoretical investigation of thermal-spin and thermoelectric properties (such as figures of merit) of MTJs driven by microwave fields [13], but also paves the way for utilizing spin caloritronics in microwave imaging applications [15,16].…”
Section: Introductionmentioning
confidence: 93%
“…Studies have found that thermoelectric effects in MTJs can be significant, with Seebeck coefficients up to S ¼1 mV/K reported at room temperature [8][9][10]12], which is several orders of magnitude larger than the values in bulk metal materials. As a result, the Seebeck rectification may allow the detection of microwaves with powers on the order of a few 10 nano-Watt [15]. Fig.…”
Section: The Physics Of Seebeck Rectificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This subsurface imaging is attractive for nondestructively detecting embedded defects and/or concealed threats. [9][10][11][12][13] Recent investigation in spintronics has explored the possibility to measure the scattered microwave using a single spintronic device, [7,8] and demonstrated that the spintronic technique allows a real-time measurement of both the amplitude and phase of microwaves to be made with high sensitivity in a large dynamic range using a magnetic tunnel junction (MTJ) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Different from the resonant microwave detection occurring in the vicinity of the ferromagnetic resonance, where an external magnetic field is usually required, the non-resonant detection allows spintronic devices to perform broadband microwave measurements in the absence of any external applied magnetic field and may move spintronic devices towards practical microwave applications such as microwave imaging. [4][5][6][7][8] Microwave radiation can propagate through large distances in space and has modest attenuation when passing through physical barriers such as clothing, plastics, soil, sand, and rocks. Thus microwaves can interact with subsurface structures in addition to structures on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%